Eperitrozoonosis (E. ovis) en ovinos y caprinos en Cuba - Joa, R.=700 1 Merino, N.; Alonso, M.
(Es, En)
Ilus., 7 ref.
Keywords: ENFERMEDADES PARASITARIAS; EPERYTROZOON; BACTERIA; OVINOS; CAPRINOS; CUBA